Molecular assessment of Coxiella burnetii in horses in Northwestern Iran - Somayyeh Hosseinzadeh; Katayoon Nofouzi; Faezah Hasanzadeh; Saber Esmaeili; Esmail Ayen (Iranian Journal of Microbiology)
Background and Objectives: Q fever is a frequently occurring illness that is induced by the bacterium Coxiella burnetii (C. burnetii) that can infect humans and various animals. It targets the macrophage cells in the tissues, and circulating monocytes. Materials and Methods: This study was conducted between 2022 and 2023 in the West Azerbaijan and Ardabil provinces of northwestern Iran to examine the presence infection of C. burnetii. Specimens were obtained by swabbing from 140 mares (70 from each province) and 20 stallions (10 from each province) which were apparently healthy, and their DNA was analyzed using quantitative PCR assay detecting the IS1111 element of the bacterium. Results: The findings indicated that a mere 0.625% of the examined specimens tested positive for C. burnetii. Among the entire set of specimens, a single female horse from the region of Ardabil was found to be the carrier of the bacterium. Conclusion: This suggested that even though horses may not display any clinical symptoms, they can still harbor C. burnetii and contribute to its transmission. Therefore, the potential contribution of horses to Q fever transmission should be considered.